THE ROLE OF POSYANDU IN REDUCING STUNTING RATES IN JATI VILLAGE, SIDOARJO REGENCY - Islami, Sovia Cahayanti; Mursyidah , Lailul (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to describe and analyse the role of integrated health service posts (posyandu) in reducing stunting in Jati Village, Sidoarjo District, Sidoarjo Regency. Method: This study used a qualitative descriptive method, data collection techniques including observation, interviews and documentation, and data analysis using Miles and Huberman's descriptive analysis, which includes data presentation, data reduction and verification. Results: The role of Posyandu as a motivator has been very effective through the implementation of various comprehensive educational and outreach activities. The role of Posyandu as a facilitator has been implemented very well through the provision of adequate facilities, infrastructure, and health services. Third, the role of Posyandu as a mobiliser has been very effective in mobilising and coordinating various community resources for stunting prevention. The role of motivator raises community awareness and motivation, the role of facilitator provides the means and services to realise this motivation, and the role of mobiliser mobilises all elements of the community in a collective movement to prevent stunting.  Novelty: This study uses a comprehensive theoretical framework from Tjokroamidjojo's role theory, which classifies organisational roles into three dimensions (motivator, facilitator, and mobiliser) to analyse the working mechanisms of Posyandu in stunting prevention, unlike previous studies that tended to be descriptive or evaluative of programmes without a strong theoretical basis.